The Idealized Brazilian Health System versus the real one: contributions from the nursing field - Dirce Stein Backes; Martha Helena Teixeira de Souza; Mara Teixeira Caino Marchiori; Juliana Silveira Colomé; Marli Terezinha Stein Backes; Wilson Danilo Lunardi Filho (Universidade de São Paulo, 2014)
OBJECTIVE: to identify the perceptions of professionals working in a facility connected with the Brazilian Unified Health System - SUS in regard to what they know, think and talk about public health policy.METHOD: this exploratory-descriptive study with a qualitative nature was conducted with 28 professionals working in a facility connected with the SUS. Data were collected through interviews with guiding questions and analyzed through the thematic content analysis technique.RESULTS: coded and interpreted data resulted in three thematic axes: The SUS - perfect web that does not work in practice; The recurrent habit of complaining about the SUS; The need to rethink the way of thinking about, acting in and managing the SUS.CONCLUSION: the professionals working for the SUS are aware of the principles and guidelines that govern the Brazilian health system, however, they reproduce a dichotomous and linear model of conception and practice strongly linked to the thinking of society in general.